Deconfinement Guidelines : What You Should Know in Times of Crisis - Seniors Action Quebec (SAQ) (2020)

COVID-19 Survey Report - Gaumond, Annie (Literacy Quebec, 2020)
On June 16, 2020, Literacy Quebec sent out an online survey to 11 member organizations. We asked about the needs and challenges of students, volunteers, and the organization, as well as the experience of working remotely during the COVID-19 pandemic. The survey closed on June 30, 2020 with a 100% response rate. We are pleased to share the summarized responses.

Activity Report 2019-2020 - Jamaica Association of Montreal (JAM) (2020)

Annual Report 2019/2020 : 40th Anniversary Edition - Literacy Quebec (LQ) (Literacy Quebec, 2020)

Celebrating 40 Years - Literacy Quebec (LQ) (2020)
The year was 1980 and the world was undergoing massive change. CNN launched, the Rubik’s cube went on sale and the Iran-Iraq war began. Closer to home, Quebecers voted in a sovereignty referendum to remain part of Canada, while the sports scene saw the Montreal Canadiens fail in their quest for a fifth consecutive Stanley Cup. But something else historic was also brewing in the province that year: Laubach Literacy Canada-Quebec (LLC-Q), the forerunner of Literacy Volunteers of Quebec, now known as Literacy Quebec.